Risk factors associated with recurrence of Henoch–Schonlein purpura: a retrospective study - Cao, Tongtong; Yang, Hui-min; Huang, Jing; Hu, Yan (Frontiers in Pediatrics, 2023)
Background: The recurrence is considered a vital problem for assessing the prognosis of Henoch–Schonlein purpura (HSP). The objective of this study was to evaluate factors affecting the recurrence in children with HSP. Methods: We retrospectively reviewed records of 368 patients under age 16 diagnosed with HSP from October 2019 to December 2020 in Beijing Children’s Hospital. Patients were divided into nonrecurrence group and recurrence group according to whether recurrence. Incidence of manifestation, possible cause, age, and treatment were retrospectively analyzed. Univariate and multivariate logistic regression analyses were used to determine the risk factors of the recurrence in HSP. Results: Percentages of patients were 65.2% for the nonrecurrence group and 34.8% for the recurrence group. The percentage of patients with renal involvement was significantly higher in the recurrence group (40.6%) than in the nonrecurrence group (26.3%). The respiratory tract infection was the most frequent trigger (67.5% in the no recurrence group and 66.4% in the recurrence group). It was more likely to have a recurrence in patients aged >6 years (53.3% vs. 71.9%). Logistic regression analysis revealed that hematuria plus proteinuria was an independent risk factor for the recurrence of HSP. On the contrary, animal protein, exercise restriction, and age ≤ 6 years were independent favorable factors for nonrecurrence of HSP. Conclusion: These results suggest that organ involvement, exercise, and diet management during the initial episode of HSP should be strictly monitored for children with HSP. Adequate clinical intervention for these risk factors may limit or prevent HSP recurrence. Moreover, renal involvement is associated with the long-term prognosis of HSP. Keywords: Pediatric HSP, recurrence, risk factor, renal involvement,retrospective study